(untitled) (UNWE Yearbook, 2021)
The paper presents research on the correspondence of the theoretical definition and the practical understanding and application by Bulgarian candidates for political posts in the elections hold in 2014-2019 of the concept “positive election campaign”. The questions are: does the meaning that the candidates attach to the term “positive campaign” correspond to its scientifically determined theoretical definition and how do the concept and its application correlate? The hypothesis states that (1) the phrase “positive campaign” is a key statement in the rhetoric of candidates; (2) the more conquered a country turns out to be, the more often the candidates for power build their pre-election political statements on the concept; (3) most often the election candidates mean a campaign with no compromising materials or hate speech, held in a spirit of good tone and ethics, promising more effective governance and a better future when they use the concept “positive campaign”; (4) the theoretical definition of the concept needs to be further developed and conceptualized within the paradigm of positivism. The hypotheses are tested by a media monitoring which identified 130 media publications covering candidates’ statements with the phrase “positive campaign” and content analyses.